2017
DOI: 10.1111/jvim.14644
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypercalcemia Before Treatment With Hypocalcemia After Treatment in Dogs With Primary Hyperparathyroidism

Abstract: BackgroundDevelopment of hypocalcemia after treatment of hyperparathyroidism results in increased costs and risk of poorer outcomes. Previous studies have shown conflicting data about predictors of hypocalcemia after these procedures.Hypothesis/ObjectivesThe objective of this study was to investigate whether ionized calcium (iCa) concentrations before treatment are predictive of hypocalcemia or its clinical signs after surgical removal or heat ablation in dogs with primary hyperparathyroidism.AnimalsFifty‐four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
2
29
3
Order By: Relevance
“…Some authors have suggested that preoperative serum calcium concentrations are indicative of the potential risk for postoperative hypocalcemia . The current veterinary literature contains conflicting information about the value of preoperative serum iCa and tCa concentrations for predicting postoperative hypocalcemia . In our study, a higher preoperative serum iCa concentration was not associated with a more rapid decrease in serum iCa concentration or risk hypocalcemia postoperatively, but was in fact protective.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Some authors have suggested that preoperative serum calcium concentrations are indicative of the potential risk for postoperative hypocalcemia . The current veterinary literature contains conflicting information about the value of preoperative serum iCa and tCa concentrations for predicting postoperative hypocalcemia . In our study, a higher preoperative serum iCa concentration was not associated with a more rapid decrease in serum iCa concentration or risk hypocalcemia postoperatively, but was in fact protective.…”
Section: Discussioncontrasting
confidence: 60%
“…Some authors have suggested that preoperative serum calcium concentrations are indicative of the potential risk for postoperative hypocalcemia . The current veterinary literature contains conflicting information about the value of preoperative serum iCa and tCa concentrations for predicting postoperative hypocalcemia .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations